Percepción urbana: Diseño de parques accesibles para reducir las barreras urbanísticas. (2022)
The urban perception is a constant reading of a place where each user forms a personal opinion about what is experienced, however, over the years people with disabilities constantly face barriers that affect accessibility and enjoyment of the services. public spaces, distorting this perception when all people should have the same possibilities regardless of their condition. This is why the role played by parks is fundamental in the process of relating to the generation of new experiences, in addition to generating new sources of physical contact with people and with nature.